1995
DOI: 10.1161/01.cir.92.12.3513
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Shear Stress Alters Endothelial Adhesiveness

Abstract: Shear stress alters endothelial adhesiveness for monocytes; at early time points, this effect is largely due to flow-stimulated release of NO and, to a lesser extent, prostacyclin. This effect of flow occurs within 30 minutes and is probably due to alterations in the signal transduction or activation state (rather than the expression) of endothelial adhesion molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
2
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(85 citation statements)
references
References 33 publications
4
77
2
2
Order By: Relevance
“…24,25 Perfusion of vein with either the nonselective potassium channel blocker TEA or the K ATP channel blocker glibenclamide did not alter the downregulation of thrombomodulin in response to arterial flow conditions (Table 1). A role for calcium in transducing signals from increased shear stress also should be considered because the application of shear stress to cultured endothelial cells increases intracellular calcium concentrations.…”
Section: Discussionmentioning
confidence: 98%
“…24,25 Perfusion of vein with either the nonselective potassium channel blocker TEA or the K ATP channel blocker glibenclamide did not alter the downregulation of thrombomodulin in response to arterial flow conditions (Table 1). A role for calcium in transducing signals from increased shear stress also should be considered because the application of shear stress to cultured endothelial cells increases intracellular calcium concentrations.…”
Section: Discussionmentioning
confidence: 98%
“…31 Aji and colleagues 9 recently reported that oral L-arginine for 6 months prevented xanthoma development and inhibited atherosclerosis in LDL cholesterol receptor knockout mice, suggesting that this response may be mediated by NO. Moreover, long-term administration of supplementary dietary arginine markedly inhibits intimal lesion formation in hypercholesterolemic rabbits 32 and preserves endothelium-dependent vasodilatation.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) is generated by endothelial nitric oxide synthase (eNOS), and has an important function in the regulation of vascular tone by inhibiting vascular smooth muscle contraction and affecting endothelial-leukocyte interaction by inhibiting platelet aggregation and leukocyte adhesion to the endothelium. 2,3 Hepatic blood flow usually is under the control of eNOS, which is present in sinusoidal endothelial cells. 4 Endothelial cell injury and dysfunction usually develop after transplant.…”
Section: Introductionmentioning
confidence: 99%